Daglige møder mellem etnicitet og klasse i en bydel - Christensen, Ann-Dorte; Qvotrup Jensen, Sune (Arbejderhistorie, 2012)
Ann-Dorte Christensen and Sune Qvotrup Jensen: Daily Meetings between Ethnicity and Class in an Urban Area, Arbejderhistorie 3/2012, pp. 1-18. The article focuses on the important dimensions in contemporary social differentiation created in the meeting between ethnicity and class. As its point of departure it takes everyday life in the stigmatized urban district of Aalborg East, which is characterized by what the French sociologist Loïc Wacquant calls territorial stigmatization. Emphasis is given to the significance of the ethnic and class based differences which are formed in the daily interaction among the residents. A socio-cultural class approach is adopted, with particular attention given to the significance a change in class has for ethnic minorities, where transnational migration often results in a displacement of social position. Through an empirical sociological analysis the dividing lines between daily life and social demarcation are thematized, amongst other things, in relation to what is understood as respectable behaviour. It is shown in the article that there is a particular challenge connected to the preservation of one’s class position when it comes to migration. Many migrants have experienced a fall in class position, which leads to a loss of status and to problems of feeling ´at home` where one comes to live in the new country. This in turn often creates a wish or an expectation among immigrants that they can restore their family status and former class position through their children. By recounting stories from the city district the article reveals how this can result in a paradoxical feeling of belonging because many parents want to ´shield` their children from the class influences in the place they live, and instead endeavor to ensure that their children are able to master Danish middle class norms.